PENGARUH INTENSITAS MENGAKSES AKUN X @PRABOWO DAN CITRA POLITIK PRABOWO SUBIANTO PADA PEMILU 2024 - Andrea Oktavia, Helga; Pradekso, Tandiyo; Surayya Ulfa, Nurist (Interaksi Online, 2024)
This study explores the influence of accessing @prabowo's account on platform X and Prabowo Subianto's political image on voter intention in the 2024 elections. Using an explanatory quantitative approach with purposive sampling of 100 respondents aged 17-40 who use X and have accessed @prabowo's account, the findings indicate that both the intensity of accessing @prabowo's account (β = 0.200, p < 0.001) and Prabowo Subianto's political image (β = 0.656, p < 0.001) positively impact voter intention. These results align with the Media Dependency Theory and the Low Information Rationality theory, emphasizing the roles of social media and political image in shaping voter attitudes.